Nodjmet A, Daughter of Amenhotep, Wife of Piankh and Mother of Herihor - Thijs, Ad (Zeitschrift für ägyptische Sprache und Altertumskunde, 2013)
For Queen Nodjmet two funeral papyri are known. In this article it is argued that both should be ascribed to the mother of Herihor (Nodjmet A) rather than to his wife (Nodjmet B). This would make Nodjmet A the wife of HPA Piankh, and her mother, Hrere, the wife of HPA Amenhotep. Hrere, who is attested with the title “king’s mother”, is here interpreted as the mother of king Khakheperre Pinuzem and as the grandmother of both Nodjmet B and HPA Masaharta. This model is discussed in the light of the Late Ramesside Letters, the Oracle of Herihor, the Banishment Stele, the Procession scene from the Temple of Khonsu and several other sources.